Regional migration and trapping frameworks in the frontier ceduna sub-basin: new insights from stratigraphic forward modelling and 'triangle juxtaposition' diagrams. Issue 1 (1st December 2018) - Langhi, Laurent; Frery, Emanuelle; Strand, Julian; Ross, Andrew
Abstract : Despite a recent renewal in exploration, the Ceduna Sub-basin is underexplored with high uncertainty regarding lithofacies distribution. This results in limited understanding of reservoir and top seal coupling, trends for fluid migration and structural trapping for the Late Cretaceous marine and deltaic interval. In order to address these uncertainties a stratigraphic forward model was developed to recreates the development and preservation of stratigraphic successions. Over an area of interest in the centre of the sub-basin, an early investigation tool consists in a rapid screening of the stratigraphic forward model to forecast vertical and lateral stratigraphic trends which outline structural trapping opportunities. The model shows an overall north-west to south-east net-to-gross distribution trend and stacked reservoir-seal successions predicted in both the marine and deltaic intervals. Structural trapping potential was assessed with Shale Gouge Ratio calculation and triangle diagrams. The marine-dominated Tiger and lower Hammerhead Supersequences are predicted with the higher potential for structural traps with probability of juxtaposition and membrane fault seals. A predicted sand-rich Early Campanian nearshore marine sequence is likely to act as a migration fairways.